Fractures and resilience of agri-food value chains in the context of COVID-19: A review of recent evidence - Stoian, D.; Marenya, Paswel Phiri; Donovan, J.; Pamerneckyte, G. (CIFOR-ICRAF, 2021)
The COVID-19 pandemic is a shock that, suddenly and unpredictably, has led to disruptions in agri-food value chains. Value chain actors have been facing the effects of both the pandemic and measures to limit the spread of the virus. Policy makers, as well as NGOs, have adopted mitigating policies, strategies, and interventions to minimize disruptions, absorb supply and demand shocks, provide relief to affected producers and consumers, and support the recovery of food chains.